(untitled) (Journal of Student Affairs in Africa, 2023)
This article reports on a qualitative study that explored self-care practices among first-year students in managing stressors related to the first-year experience in the context of the COVID-19 pandemic. Qualitative data were collected using a purposive sample between March and June 2022. A total of 26 first-year students registered at a university of technology in South Africa participated in the study by producing digital stories sharing how they practised self-care. The domains of self-care were adopted as a framework and data were analysed using thematic analysis. Six domains of self-care practices emerged from the data and were categorised as physical, emotional, spiritual, relational, professional, and psychological. The findings show that first-year students engaged in a range of self-care practices across the domains of self-care including exercising, listening to music, performing ancestral rituals, donating blood, following successful people on social media, and learning new skills. Further, relational self-care was the most fundamental domain that underpinned first-year students’ well- being. In contrast, oversleeping or sleep deprivation, reckless spending, and eating unhealthy food to cope with stressors related to the first-year experience pointed to unhealthy self-care practices in managing the stressors. Unhealthy self-care practices can threaten first-year students’ well-being and possibly academic success. Student affairs and services need to design self-care programmes and curricula to prevent harm and support adequate self-care. In designing self-care programmes, social involvement and engagement are fundamental principles that should be emphasised. Future studies can develop a self-care inventory to identify students at risk of poor self-care and design targeted interventions to promote self-care.